2017
DOI: 10.2967/jnumed.117.190827
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA-11 PET/CT Interobserver Agreement for Prostate Cancer Assessments: An International Multicenter Prospective Study

Abstract: The interobserver agreement for Ga-PSMA-11 PET/CT study interpretations in patients with prostate cancer is unknown.Ga-PSMA-11 PET/CT was performed in 50 patients with prostate cancer for biochemical recurrence ( = 25), primary diagnosis ( = 10), biochemical persistence after primary therapy ( = 5), or staging of known metastatic disease ( = 10). Images were reviewed by 16 observers who used a standardized approach for interpretation of local (T), nodal (N), bone (Mb), or visceral (Mc) involvement. Observers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
96
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 38 publications
19
96
0
2
Order By: Relevance
“…6 clearly shows improvement in each category where κ statistics were determined. This was in concordance with the interobserver agreement study by Fendler et al [27] who also found that observers with less than 30 previous PSMA image readings only showed moderate interrater reliability contrary to more experienced observers who achieved substantial to almost perfect agreement. Retrospectively, all observed lesions from the original Phase 2 were discussed with both observers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…6 clearly shows improvement in each category where κ statistics were determined. This was in concordance with the interobserver agreement study by Fendler et al [27] who also found that observers with less than 30 previous PSMA image readings only showed moderate interrater reliability contrary to more experienced observers who achieved substantial to almost perfect agreement. Retrospectively, all observed lesions from the original Phase 2 were discussed with both observers.…”
Section: Discussionsupporting
confidence: 92%
“…It may be more appropriate to administer a lower furosemide dose simultaneously with the radiotracer administration for the comfort of the patient, which is also recommended in the guidelines of EANM and SNMMI for administration of 68 Ga-PSMA [14]. PSMA expression is not specific to the prostate only; physiological background uptake is seen in the kidneys, bladder, intestines, and salivary glands as well as in pathological conditions such as Paget's bone disease and neovasculature of several solid tumours such as highgrade sarcomas [27][28][29][30][31]. Moreover, some prostatic malignant lesions exhibit minimal PSMA expression and can be difficult to detect on PET [32].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent data on 68 Ga-PSMA-11 PET/CT showed that increasing reader experience positively correlated with interreader agreement and presumably with accuracy to determine clinical stage. 25 The specificity of 18 F-DCFPyL PET/CT may also be improved through concurrent use of pelvic MRI, multiple imaging time points and/or administration of diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…Standard image reconstruction parameters were used (16,18). 68 Ga-PSMA-11 PET/CT Image Analysis 68 Ga-PSMA-11 PET/CT images were analyzed according to recent guidelines during clinical readouts by an experienced nuclear medicine physician who had unlimited access to all medical records (16,18,19): any focal uptake of 68 Ga-PSMA-11 PET/CT above the background level and not associated with physiologic uptake or known pitfalls (6,18) was considered PSMA-positive.…”
Section: Survey Designmentioning
confidence: 99%
“…Compar ed with conventional imaging, 68 Ga-PSMA-11 PET/ CT is superior for detecting sites of prostate cancer biochemical recurrence (BCR) (1)(2)(3)(4), is sensitive for detecting regional and distant metastatic disease (3,5), is highly specific (4,) and is associated with a low interreader variability (6).…”
mentioning
confidence: 99%